P423 Comparative efficacy of anti-tumour necrosis factor agents and vedolizumab in ulcerative colitis. (25th January 2019) - Subramanian, S; Davis, R; MacParland, P; Dodd, S; Storey, D; Probert, C; Collins, P; Skouras, T; Steel, A; Derbyshire, E; Dibb, M
Abstract: Background: Anti-tumour necrosis factor (TNF) agents and vedolizumab are used to treat UC but response is variable and there are little data on comparative efficacy of these agents. Apart from prior exposure to anti-TNF agents and concurrent immunomodulatory therapy, predictors of clinical response and remission to biologics have not been identified. We aimed to (i) compare the efficacy of anti-TNF agents and vedolizumab as induction and maintenance therapy in UC and (ii) investigate the utility of routinely used clinical and biochemical parameters in predicting clinical response and remission to biologics. Methods: Patients who were commenced on any biological agent for ambulant UC were included in this single-centre cohort study. Disease activity was monitored serially by calculation of Simple Clinical Colitis Activity Index (SCCAI) for up to 12 months. Faecal calprotectin (FC) at baseline and subsequent visits were recorded if available. Clinical response was defined as decrease in SCCAI ≥3 and remission by SCCAI ≥2. We compared the efficacy of anti-TNF agents and vedolizumab for induction and maintenance of response on an intention-to-treat basis. We also examined the utility of FC and early normalisation of FC to predict response and remission at 6 and 12 months. Results: Ninety-seven patients commencing anti-TNF and 42 commencing vedolizumab therapy were included. Vedolizumab-treated patients had greater rate of prior anti-TNF therapy (69% vs. 11.3%, p = 0.001) and a lower baseline FC (median 577µg/g, IQR 72–210 vs. 955µg/g, IQR 116–2100 vs. p = 0.005). Clinical response, remission and steroid-free remission rates were broadly comparable between anti-TNF and vedolizumab-treated patients at 6 weeks, 6 and 12 months. Clinical remission at 12 months was higher in the vedolizumab group (51.4% vs. 27.8%, 27.8%, difference 95% CI 4.8–42.4) but no difference was noted in steroid-free remission at 12 months. There was a significant weekly reduction in SCCAI for vedolizumab (−0.06, 95% CI −0.09 to −0.04, p < 0.001) and anti-TNF agents (−0.06, 95% CI −0.07 to −0.04, p < 0.001). Similarly, the weekly calprotectin dropped significantly for vedolizumab (−7.64 µg/g, 95% CI −12.82 to −2.45, p = 0.004) and anti-TNF agents (−17.43 µg/g, 95% CI −23.79 to −11.08, p < 0.001). The colectomy rate (9.5% vedolizumab, 4.1% anti-TNF) and treatment persistence rate at 12 months (73% vedolizumab, 71% anti-TNF) were comparable between the two groups. None of the clinical and biochemical variables including baseline and early normalisation of FC predicted remission at 6 and 12 months. Conclusions: In a single-centre series of biologic-treated UC patients, the efficacy of anti-TNF and vedolizumab appear comparable. We could not identify any predictors of response and remission.